Arthroscopic hip surgery in the elite athlete: Comparison of female and male competitive athletes - Shibata, K. R.; Matsuda, S.; Safran, M. R. (The American Journal of Sports Medicine, 2017)
Methods: Data on all elite athletes who underwent primary hip arthroscopic surgery between 2007 and 2014 were included. Athletes with a Hip Sports Activity Scale (HSAS) score of over 6 were identified. The preoperative evaluation included a medical history, history of sports activity, and hip-specific outcome scores (Modified Harris Hip Score [MHHS] and International Hip Outcome Tool-33 [iHOT-33]). Surgical findings and time to return to competitive sports were documented. Results: Of 547 hips in 484 consecutive patients, 98 elite athletes (49 female) with a mean follow-up of 18.9 ± 12.8 months were identified. Eighty patients desired to return to their original competitive activity: 38 were female (42 hips; mean age, 21.5 ± 3.9 years), and 42 were male (54 hips; mean age, 20.5 ± 1.9 years). Moreover, 84.2% of female athletes and 83.3% of male athletes were able to return to the same level of competition at a mean of 8.3 ± 3.0 and 8.8 ± 2.9 months, respectively. Significant improvements between preoperative and postoperative outcome scores were seen in both groups (all P < .0001). Female athletes had more pincer femoroacetabular impingement (FAI) (P = .0004) and instability (P < .0001). Conversely, male athletes were diagnosed more commonly with combined FAI (P < .0001), demonstrated greater acetabular cartilage damage (P = .0004), and required microfracture more often (P = .0014). Female athletes competed more frequently in flexibility (4/38, 11%; P = .047) and endurance (9/38, 24%) sports, while male athletes participated in cutting (14/42, 33%), contact (6/42, 14%), and asymmetric (13/42, 31%) sports more often. Patients who returned to their baseline level of competition had a shorter duration of symptoms preoperatively (P = .001). Microfracture status did not affect the ability to return to sports. Conclusion: Female and male elite athletes were able to return to competitive sports activity at the same or higher level after hip arthroscopic surgery at a similar rate, although their performance in sports was not measured. Distinct differences in the diagnosis, treatment, and type of sports activity between sexes were seen. The duration of symptoms negatively correlated with outcomes. Microfracture did not affect the return to sports.